Forensic Autopsy Experience and Core Entrustable Professional Activities: A Structured Introduction to Autopsy Pathology for Preclinical Student. (1st March 2019) - Kemp, Walter L.; Koponen, Mark; Sens, Mary Ann
The forensic and autopsy pathology service within the Department of Pathology at University of North Dakota School of Medicine provides an optional, structured autopsy experience for medical students during the second year of the curriculum. This experience reinforces forensic autopsy pathology as the practice of medicine and highlights the American Association of Medical Colleges Core Entrustable Professional Activities. Students self-select for this optional, noncredit autopsy observership. Prior to the experience, interested students participate in a session that reviews the professional and educational expectations of the autopsy experience, autopsy safety training, and logistics of call. Groups of up to 4 students are on call for an autopsy. Student groups observe and participate in an autopsy, ideally from scene through autopsy performance, slide review, and toxicology results. The student groups use a structured presentation format for summarizing their autopsy experience, forming a differential and final diagnosis, completing the death certificate, and discussing quality management or learning issues in the case. At the end of the semester, all students participating in the experience meet and each group presents a 10-minute, structured review of their case. At least 6 core entrustable professional activities were addressed in every autopsy review; some had more when advanced clinical questions or safety issues were identified. Additionally, one student presented his case at a national meeting with a resultant publication. The experience provided (1) a positive introduction to autopsy pathology, (2) reinforced the role of pathology in medicine, and (3) provided concrete examples of American Association of Medical Colleges Core Entrustable Professional Activities within pathology for students in preclinical years.